TESTING INTRADAY VOLATILITY SPILLOVERS IN TURKISH CAPITAL MARKETS: EVIDENCE FROM ISE - (:unkn) unknown (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2013)
The aim of this article is to examine the presence of volatility transmission between futures index and underlying stock index by using intraday data in Turkey. We first examined the sudden changes in the variance of futures index return and the underlying spot index return. Then we employed the causality in the variance tests proposed by Hong (2001) and Hafner and Herwartz (2006). According to the empirical results, the spot market was found to be Granger cause of futures market and this result suggests that the spot market plays a more dominant role in the price discovery process in Turkey.
Keywords: Spot and Futures Markets; Structural Breaks in Variance; Volatility Spillovers; Intraday Data; Causality in Variance; STOCK INDEX FUTURES; LEAD-LAG RELATIONSHIP; PRICE DISCOVERY; TIME-SERIES; UNIT-ROOT; CAUSALITY; SPOT; VARIANCE; INFORMATION; TRANSMISSION